Solubility of Ca(ii), Ni(ii), Nd(iii) and Pu(iv) in the presence of proxy ligands for the degradation of polyacrylonitrile in cementitious systems. Issue 24 (8th June 2022) - Szabo, P. G.; Tasi, A. G.; Gaona, X.; Polly, R.; Maier, A. C; Hedström, S.; Altmaier, M.; Geckeis, H.
Abstract : The solubility of Ca(OH)2 (cr), β-Ni(OH)2 (cr), Nd(OH)3 (s) and PuO2 (ncr, hyd) was investigated in cement porewater solutions containing glutarate, α-hydroxyisobutarate and 3-hydroxybutarate as proxy ligands for the degradation of polyacrilonitrile. Abstract : The solubility of Ca(OH)2 (cr), β-Ni(OH)2 (cr), Nd(OH)3 (s) and PuO2 (ncr, hyd) was investigated in cement porewater solutions containing glutarate (GTA), α-hydroxyisobutarate (HIBA) and 3-hydroxybutarate (HBA). These ligands were proposed as probable degradation products of UP2W, a polyacrylonitrile-based filter aid used in nuclear power plants. Results obtained in this work are compared with reported solubility data in the presence of iso-saccharinic acid (ISA), a polyhydroxocarboxylic acid resulting from cellulose degradation. None of the investigated proxy ligands shows any significant impact on the solubility of Ca(ii ), Nd(iii ) or Pu(iv ) in cement porewater solutions. Although the formation of binary complexes M–L (M = Ca(ii ), Nd(iii ), An(iv ); L = GTA, HIBA, HBA) under acidic conditions is described in the literature, these organic ligands cannot outcompete hydrolysis under hyperalkaline conditions. GTA, HIBA and HBA induce a slight increase in the solubility of β-Ni(OH)2 (cr) at [L]tot = 0.1 M. This observation supports the formation of stable Ni(ii )–GTA, –HIBA and –HBA complexes in hyperalkaline conditions, although the exact stoichiometry of these complexes remains unknown. The comparison of these results with solubility data in the presence of ISA confirms the stronger complexation properties of the latter ligand. Even though HIBA and HBA are carboxylic acids containing one alcohol group, this comparison shows that additional alcohol groups are required to efficiently chelate the metal ion and outcompete hydrolysis. This conclusion is supported by DFT calculations on the Pu(iv )-OH–L systems (L = GTA, HIBA and HBA), which indicate that the complexation with the proxy ligands takes places through the carboxylate group. XRD of selected solid phases after equilibration with proxy ligands at [L]tot = 0.1 M confirms that Ca(ii ), Ni(ii ), Nd(iii ) and Pu(iv ) starting solid materials remained mostly unaltered in the course of the experiments. However, the presence of new XRD features suggests the possible formation of secondary phases. These results allow assessment of the effect of the proposed proxy ligands on the solubility of key radionuclides and metal ions in cementitious systems relevant for low and intermediate level waste, and feed into on-going sorption studies evaluating the impact of UP2W degradation products on the uptake of radionuclides by cement.